Challenges and Constraints: Examining Women Politicians' Status in Decision-Making within Political Parties - Dhakal, Naba Raj; Thapa, Khusboo (Bhairahawa Campus Journal, 2024)
This study examines the challenges faced by women politicians in Nepal, focusing on their participation in decision-making processes within political parties. Despite constitutional provisions for gender equality, women are often marginalized in politics due to societal and familial constraints. Men benefit from these dynamics, as they are able to engage freely in political activities, while women are restricted by traditional gender roles and the need for family approval. This paper aims to investigate the decision-making status of women politicians and the factors that constrain them. This research article explores the status of women politicians in decision-making procedures within the political parties and the constraining factors that place the women in the position of subordination. Twenty participants were selected applying the simple random sampling method that falls under the probability sampling. Five women members were selected from each party, such as the Nepali Congress Party, CPN (UML), Maoist Party, and National Democratic Party, from the Siddarthanagar Municipal Committee using the lottery method. The semi-structured interview schedule was employed as the tool to collect the data. The study highlights that, although there is a growing presence of women in leadership positions, their opinions are often undervalued, particularly in male-dominated environments. A significant number of women (60%) report feeling neglected in discussions on gender-sensitive issues, such as reproductive rights and gender-based violence. Additionally, women face widespread distrust in their leadership abilities, with factors like gender bias, societal expectations, and financial constraints hindering their political advancement. Practices of favoritism and nepotism further limit opportunities for women.